Learning C♯ 2005 - Liberty, Jesse (O'Reilly, 2006)
If you're a novice programmer and you want to learn C♯, there aren't many books that will guide you. Most C♯ books are written for experienced C++ and Java programmers. That's why Jesse Liberty, author of the best-selling books Programming C♯ and Programming ASP.NET, has written an entry-level guide to C♯. Written in a warm and friendly manner, Learning C♯ assumes no prior programming experience, and provides a thorough introduction to Microsoft's premier .NET language. The book helps you build a solid foundation in .NET, and shows you how to apply your skills through the use of dozens of tes.